2005
DOI: 10.1080/02770900500371294
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone Propionate HFA-134a Pressurized Metered-Dose Inhaler in Adolescents and Adults with Moderate to Severe Asthma

Abstract: In this randomized, double-blind, placebo-controlled trial, 397 patients with moderate to severe asthma, previously treated with bronchodilators alone, received fluticasone propionate 88, 220, or 440 microg twice daily, or placebo via metered dose inhaler (MDI) for 12 weeks. Mean change from baseline to endpoint in pre-dose percent predicted forced expiratory volume in one second (FEV1) was greater (p < 0.001) in each fluticasone propionate group (9.0%, 88 microg bid; 9.8%, 220 microg bid; 11.2%, 440 microg bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Eleven studies of fluticasone propionate vs placebo and 4 studies of mometasone vs placebo were identified in the literature search (Supplemental Table S2) . The 4 mometasone studies were used for cumulative meta‐analysis and provided indirect comparison results with fluticasone propionate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies of fluticasone propionate vs placebo and 4 studies of mometasone vs placebo were identified in the literature search (Supplemental Table S2) . The 4 mometasone studies were used for cumulative meta‐analysis and provided indirect comparison results with fluticasone propionate.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies of fluticasone propionate vs placebo and 4 studies of mometasone vs placebo were identified in the literature search ( Supplemental Table S2). [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The 4 mometasone studies were used for cumulative meta-analysis and provided indirect comparison results with fluticasone propionate. The respective point estimate values of indirect comparison for FEV 1 (L) were 0.20, 0.03, 0.02, and 0.03 (Figure 3).…”
Section: Indirect Comparison Of Inhaled Corticosteroidmentioning
confidence: 99%
“…However, previous studies have shown that the HFA and CFC formulations are therapeutically comparable at equal doses in both school-age children 4 and adolescent and adult patients with asthma. [15][16][17][18][19][20] In the very young pediatric population, Wasserman et al 8 gave FP CFC 88 g or placebo twice a day through a VHC (Aerochamber Plus or Optichamber) to children age 24 to Ͻ 48 months with asthma. The mean change from baseline to endpoint for both 24-hour daily and nighttime asthma symptom scores with FP CFC was -0.7 (on a scale of 0 to 3), a significant improvement compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Pinnas et al enrolled 397 adolescents and adults with moderate-to-severe asthma inadequately controlled on short-acting bronchodilators alone [47]. Fixed doses of FP 88, 220 and 440 µg via a HFA pMDI were administered twice daily for 12 weeks and compared with placebo.…”
Section: Efficacy Trialsmentioning
confidence: 99%
“…A total of three randomized, double-blind, placebo-controlled trials were conducted in the USA to assess the efficacy and safety of FP 88, 220 and 440 µg delivered by a HFA pMDI in the treatment of asthma (TABLE 3) [32,46,47].…”
Section: Efficacy Trialsmentioning
confidence: 99%